Produção de alface americana em função do espaçamento e épocas de plantio - Sousa, Thiago Pereira de (2016)
The spacing and planting date are factors that can influence the yield of lettuce. Aiming to evaluate the production of American lettuce in relation to spacing and planting season were conducted four experiments in the garden of Departamento de Ciências Vegetais da Universidade Federal Rural do Semi-árido (UFERSA), campus de Mossoró-RN. Each experiment was carried out in the field at a season of planting: 12/23/2014 (summer), 03/25/2015 (autumn), 06/22/2015 (winter) and 09/23/2015 (spring). The characteristics evaluated were height and plant diameter (cm), number of leaves (plant-1), fresh and dry weight of plants (g plant-1), and productivity (t ha-1). The experimental design was a randomized complete block in a factorial 2 x 4 with two lettuce cultivars (Angelina and Amelia) and four planting spacings (15 x 15 cm, 20 x 20 cm, 25 x 25 cm and 30 x 30 cm) and three replicates. Increased planting density resulted in higher productivity, although with lower average mass of plants. The winter and summer crops were best suited for the cultivars, providing the highest productivity